1968
DOI: 10.1063/1.1656884
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Stiffness Coefficients of Single-Crystal Iron from Room Temperature to 500°C

Abstract: The three adiabatic second-order elastic stiffness coefficients of single-crystal iron are reported from room temperature to 500°C. The coefficients vary in a linear manner with temperature, as opposed to previous results where a departure from linearity took place above 300°C. It seems likely now that this previous behavior was due to the silicone fluid bond between the quartz transducer and the iron specimen, and not the specimen itself. The present work shows that vacuum-evaporated thin-film transducers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 9 publications
4
25
0
Order By: Relevance
“…It is shown that thermal properties are also correctly reproduced. The calculated temperature dependence of bulk modulus shows a good agreement with experimental data, [22][23][24][25][26] as illustrated in Fig. 1.…”
Section: Interatomic Potentialsupporting
confidence: 71%
See 1 more Smart Citation
“…It is shown that thermal properties are also correctly reproduced. The calculated temperature dependence of bulk modulus shows a good agreement with experimental data, [22][23][24][25][26] as illustrated in Fig. 1.…”
Section: Interatomic Potentialsupporting
confidence: 71%
“…Fig. 1 Calculated bulk modulus of (a) pure Al and (b) pure Fe according to the 2NN MEAM interatomic potentials, [5,6] in comparison with experimental data [22][23][24][25][26] Table 2 Physical properties of various structures in the Ni-W system calculated based on the MEAM potential, [15] in comparison with experimental data or FP calculation [27] a, Å c, Å E c , eV Basic and Applied Research: Section I Fig. 2 Superstructure composed of bcc and fcc Fe used for computation of (a) the K-S interfacial energy and (b) an average value of random interfaces Fig.…”
Section: Computation Of Stacking Fault Energymentioning
confidence: 99%
“…Comparison of the elastic constants of seven pure metals obtained from polycrystalline samples of this study with those obtained from single crystals reported in the literature [29][30][31][32][33][34][35] (All values in GPa and Δ = Difference) Sample C enough for measurements. The TDTR signal is quite strong and the measurements comprised 33 grain-PDMS film orientation combinations.…”
Section: Resultsmentioning
confidence: 99%
“…More accurate C 11 and C 12 were obtained through decreasing step size and increasing the number of the initial values. The measured C ij values from all five cubic polycrystalline pure metals are summarized in Table 2 in comparison with results from single crystal measurements, [28][29][30][31][32] showing that the maximum difference is only 5.3% among all the 15 measured C ij values with the standard deviation of difference between the polycrystalline (this study) and single-crystal (the literature) measurements for C 11 , C 12 , and C 44 being 2.2, 3.2, 3.5%, respectively. The excellent agreement is graphically shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High temperature elastic constants of a-Fe has already been examined from 1931 to 1971 by several researchers. [5][6][7][8][9][10] These studies report C ij (T) in different temperature ranges while the results show inconsistency in the overlapped temperature intervals. Thus re-investigation should be worth while.…”
Section: Introductionmentioning
confidence: 99%